Potenciál využití online médií ve výuce geologie na základní a střední škole - Jedličková, Tereza; Vasilis; Denisa (Scientia in educatione, 2024)
The presented study has mapped the media representation of selected geological terms related to the educational topic of "Evolution of Organisms on Earth" and has analyzed their educational potential for lower and higher secondary school levels. The content analysis of 114 online articles from the top fifteen most-read media websites, derived from the Anopress database, has focused on the context of usage, the level of explanation of geological terms, and the usability of online articles for teaching. The results have shown that 69 % of the analyzed articles have not explained the selected geological terms according to their definitions, and 71 % of the articles cannot be used to teach the studied subject. They also indicate that commonly available online media content often provides pupils with a superficial understanding of geological terms and topics and cannot be used to form their preconceptions, rather it tends to generate misconceptions. The style and presentation of information in the media do not correspond to the needs of classroom practice.